Healing trauma - McNeily, Robert; Centre of Effective Therapy (Firm) ([Brighton North, Vic. : Centre of Effective Therapy, 2005)
Robert McNeilly discusses hypnotism using Ericksonian methods as a therapeutic tool, focussing on marital relationships. The DVD also includes a therapy session
Title on booklet: Learning solutions in hypnosis & counselling
[Psychologist] : Dr. Robert McNeilly
DVD format
Keywords: Stress (Psychology) -- Treatment; Psychic trauma -- Treatment; Hypnotism -- Therapeutic use; Psychotherapy